Efecto de la temperatura y del tiempo de lixiviación alcalina en caliente utilizando soda cáustica (NaOH) y sulfuro de sodio (Na2S), sobre la extracción de As y el grado de concentración de Cu, Au y Ag de un concentrado de enargita (Cu3AsS4) - Azañero Castillo, Golden Shamir (2016)
This experimental research the effect of temperature and time of alkali leaching hot was studied using caustic soda (NaOH) and sodium sulfide (Na2S), on the extraction of As and the degree of concentration of Cu, Au and Ag concentrate enargita (Cu3AsS4) ", the ore is from the center of Peru (province of Yauli). The concentrate showed the following chemical analysis: 21.5% Cu, 5.8% As, 254.71 g / TM Ag, 2.55 g / TM Au, each test was conducted with dilution L / S of 10 to 1, with 20 grams and 200 ml of liquid (leaching solution) at a stirring speed of 750 rpm, constantly blowing air to a particle size 86% less than 400 mesh (38um); reagents used was caustic soda (NaOH) to 3.5 molar and sodium sulfide (Na2S) to 1.0 molar. A factorial design follows were evaluated at 3 levels and 2 replicates, the temperature was considered 70, 80 and 90 ° C; time was considered 2, 3 and 4 hours with a total of 18 tests From the results it is obtained that the maximum extraction of 97.73% As is, at 90 ° C and 4 hours of leaching, remaining concentrate grade (tailings) with 23.23% Cu, 239.81 g / TM Ag, 2.52 g / mt Au and 3.07% for extraction of Au; 5.85% Ag and 0.13% for Cu. It is concluded according to the analysis of variance with a confidence level of 95% that the variables of temperature, time and their interaction significantly influence the extraction of arsenic.